Anorectal manometry under adequate sedation or anesthesia as a highly reliable diagnostic tool for Hirschsprung's disease in neonates and young infants: A multicenter retrospective study - Yohei Sanmoto; Atsuki Naoe; Yudai Goto; Mikihiro Inoue; Kouji Masumoto (Global Pediatrics, 2025)
Background: Hirschsprung's disease is a congenital disorder characterized by the absence of enteric ganglion cells. The diagnostic gold standard for Hirschsprung's disease is a rectal mucosal biopsy; however, its accuracy in neonates and young infants remains limited. Although less invasive, the diagnostic performance of anorectal manometry (ARM) in these populations remains controversial. We evaluated the diagnostic performance of ARM in patients with Hirschsprung's disease by age group. Methods: This multicenter retrospective study compared the diagnostic outcomes of ARM and biopsy across three age categories: neonates (<28 days), infants ≤6 months, and children aged >6 months. Additionally, logistic regression analysis was performed to assess changes in the probability of accurate diagnosis and exclusion of Hirschsprung's disease by ARM with increasing age. Results: Overall, 113 patients were included in this study. The median patient age (range) at the time of ARM was 103 (3–3913) days. Most patients (83.2 %) underwent ARM under intravenous sedation or inhalation anesthesia. ARM revealed higher sensitivity than did biopsy in neonates (100 % vs. 45.5 %, P = 0.012) and infants aged ≤6 months (97.1 % vs. 79.6 %, P = 0.022). With increasing age, the probability of accurate diagnosis for Hirschsprung's disease by ARM significantly decreased (P = 0.031), although the probability of accurate exclusion showed no significant change (P = 0.35). Conclusion: ARM, when performed under appropriate sedation or anesthesia, yields superior sensitivity for diagnosing Hirschsprung's disease in young children than does biopsy. However, diagnostic accuracy decreases with age, requiring careful interpretation in patients aged >6 months.